Wpływ wybranych czynników społeczno-gospodarczych na saldo migracji, ze szczególnym uwzględnieniem województwa łódzkiego - Ambroziak, Ewa; Jakubiec, Tomasz (Gospodarka w Praktyce i Teorii, 2012)
The paper presents an analysis of human migration and its main economic and social factors in Polish voivodeships. The main reason of migration is based on differences in the standards of living in different locations. Important factors indicating difference are unemployment rates, average gross wages, housing conditions and access to education. This paper also presents description of econometric model – estimation results confirm correlation between migration balance and socioeconomic factors.